Adaptation Response of Climate Fluctuation Impact: A Study from Dry Land Farmer Community - Mahawan Karuniasa; Priyaji Agung Pambudi; Alfionita Bella Pertiwi (Agriekstensia : Jurnal Penelitian Terapan Bidang Pertanian, 2021)
ABSTRACT Climate change threatens sustainability and the environment, like food production, freshwater, and air condition, especially the dryland ecosystem. Seasonal change of the rainy season and prolonged drought put pressure on the farmer community that experienced a decrease in agriculture production and difficulty in land management. This research aims to find out the dry land farmer adaptation in overcoming climate change impact. The method used was the mixed method through observation, interview, and literature review. The majority of elder farmer respondents are 51-70 years old (46,87%), while a farmer in productive age <50 years old are (34,37%). When in detail, farmer respondents in a young age of <30 years old only 6,25%. Farmer respondents in the research location have senior high school graduate education degrees (40,62%). In 2015, an extreme drought occurred, and the total rainfall was only 1,565 mm3, then in 2016, it increased to 3,817 mm3. The change of annual total rainfall, which was great, reached 243%, caused some crops not to adapt well, decreasing agriculture production and farmers' income. Monoculture-based farming patterns impose production costs that continue to increase annually, while contributions to farmer incomes continue to decrease. This matter makes the income decrease from 14% in 2013 to 10,25% in 2018. Besides that, the feasibility analysis of monoculture-based farming also decreased from 4,33 to 2,7. Therefore, the implementation of a multicultural-based farming pattern is the best for adapting the climate change. The multicultural contributes to the farmer income as many as 12,12% and farming business feasibilities of 2,86. Keywords: Agriculture, climate fluctuation, farmers, income, plant